PERAN ORANG TUA DALAM PEMBENTUKAN KEPRIBADIAN ANAK DALAM BUKU PERANAN KETELADANAN ORANG TUA DALAM MENDIDIK ANAK KARYA AMALLIAH KADIR - Basri, Hasan; Adeliyah, Nadiyah Syifa (Tamaddun : Jurnal Pendidikan dan Pemikiran Keagamaan, 2024)
The role of parents in educating children, especially in terms of religion and worship, certainly has a very important role in life. Especially for the development of an increasingly advanced era today, parents must equip themselves with good knowledge because it can be a big influence for children's education in the future. There are so many career parents out there who, of course, only have a little time with their children, moreover, mothers also work for the sole reason of wanting to help ease the burden on their husbands at home. The role of parents is important because parents are in the formation of personality for their children. Based on the research context, the problem that can be formulated is how the role of parents in shaping the child's personality in the book on the role of parental example in educating children by Amalliah Kadir. The purpose of this study is to find out how the role of parents in shaping the child's personality is contained in the book The Role of Parental Exemplary in Educating Children. This research is a type of literature study research that uses the object of literature review and the primary data source is the book The Role of Parental Exemplary in Educating Children by Amalliah Kadir. and for secondary sources take from books, journals, articles related to research. The data analysis technique is to use descriptive and content analysis. The results of this study indicate that the role of parents in shaping the child's personality in the book The Role of Parental Exemplary in Educating Children by Amalliah Kadir is to discuss how to educate children and teach good morals for children.The first education that parents need to instill in their children from a young age is aqidah, morals and worship. Besides that, being a parent is not easy because you have to have patience and patience so you don't feel stressed easily. It is even better if parents must have good qualities such as: compassionate, forgiving, intelligent, sincere and kind, patient, sincere, etc. Keywords: the role of parents, personality formation, Islamic personality